A novel e‐bike energy management for improvement of the rider metabolism - Sohrab Ebnealipour; Masoud Masih‐Tehrani; Hossein Nazemian (IET Intelligent Transport Systems, 2023)
Abstract In this study, a switch controller manages the power‐sharing between the battery and human mode to improve the rider's metabolism and manage the battery SOC. The main idea is to optimize this power source switching element for changing the status to reach a trade‐off between lack of tiredness and keeping the SOC high. Calorie burning is closely related to the rider's physical characteristics. In this paper, these parameters are investigated to calculate calorie burning. When the electric‐powered mode is activated, the SOC level comes down. When the human‐powered mode is activated, the human power source provides energy. The model converts the bicycle speed into the rider's heart rate and then changes it into burned calories based on some equations. These equations are obtained by poly fitting after experiments. This optimization causes 33.5% and 50% burning calorie reduction in Cleaveland and Portuguese driving cycles. Also, in the Portuguese driving cycle, the battery usage percentage decreases 39.56% from to 20.54% after optimization; therefore, the burning calorie decreases 265.84 Kcal to 176.83 Kcal.